2022
DOI: 10.3390/s22072472
|View full text |Cite
|
Sign up to set email alerts
|

A Multimodal Approach for Real Time Recognition of Engagement towards Adaptive Serious Games for Health

Abstract: In this article, an unobtrusive and affordable sensor-based multimodal approach for real time recognition of engagement in serious games (SGs) for health is presented. This approach aims to achieve individualization in SGs that promote self-health management. The feasibility of the proposed approach was investigated by designing and implementing an experimental process focusing on real time recognition of engagement. Twenty-six participants were recruited and engaged in sessions with a SG that promotes food an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…This progression comes naturally with the increasing adoption of connected devices, including wearable and nonwearable sensors, as part of the AI-driven serious game. With this in mind, we project that AI-driven serious games will be more adaptable in an unobtrusive and affordable manner [94]. This review found that 3D serious games were slightly more common than 2D serious games, which is in line with the findings of a previous review [36].…”
Section: Principal Findingssupporting
confidence: 77%
See 1 more Smart Citation
“…This progression comes naturally with the increasing adoption of connected devices, including wearable and nonwearable sensors, as part of the AI-driven serious game. With this in mind, we project that AI-driven serious games will be more adaptable in an unobtrusive and affordable manner [94]. This review found that 3D serious games were slightly more common than 2D serious games, which is in line with the findings of a previous review [36].…”
Section: Principal Findingssupporting
confidence: 77%
“…This progression comes naturally with the increasing adoption of connected devices, including wearable and nonwearable sensors, as part of the AI-driven serious game. With this in mind, we project that AI-driven serious games will be more adaptable in an unobtrusive and affordable manner [ 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…The low engagement with the ENDORSE’s SG highlights the great challenge of designing an SG featuring a balance between user attractiveness and scientific background in accordance with the existing literature [ 53 , 54 , 55 ]. However, the significant enhancement that was observed in terms of engagement in the pilot version compared to the pre-pilot version supports the effectiveness of the SG’s gameplay flow and conceptual framework.…”
Section: Discussionmentioning
confidence: 83%
“…For FAA, this was shown to elicit weaker activity patterns than multimodal stimuli that most of the previous studies employed [25]. Neural synchronization may also be diminished due to this unimodal approach, since engagement in general was higher with multimodal design [26].…”
Section: Discussionmentioning
confidence: 86%